Ancient evolutionary origins of epigenetic regulation associated with posttraumatic stress disorder - Sipahi, Levent; Uddin, Monica; Hou, Zhou-Cheng; Aiello, Allison E.; Koenen, Karestan C.; Galea, Sandro; Wildman, Derek E. (Frontiers in Human Neuroscience, 2014)
Epigenetic marks, including DNA methylation, are modifiable molecular factors that may underlie mental disorders, especially responses to trauma, including the development of and resilience to posttraumatic stress disorder (PTSD). Previous work has identified differential DNA methylation at CpG dinucleotide sites genomewide between trauma exposed individuals with and without PTSD, suggesting a role for epigenetic potential – the capacity to epigenetically regulate behavior and physiology in response to lived experiences. The human species is characterized by an increased period of adaptive plasticity during brain development. The evolutionary history of epigenetic potential in relation to adaptive plasticity is currently unknown. Using phylogenetic methods and functional annotation analyses, we trace the evolution of over 7,000 CpG dinucleotides, including 203 associated with PTSD, during the descent of humans in during mammalian evolution and characterize the biological significance of this evolution. We demonstrate that few (7%) PTSD-associated CpG sites are unique to humans, while the vast majority of sites have deep evolutionary origins: 73% and 93% were unambiguously present in the last common ancestor of humans/orangutans and humans/chimpanzees, respectively. Genes proximal to evolved PTSD-associated CpG sites revealed significant enrichment for immune function during recent human evolution and regulation of gene expression during more ancient periods of human evolution. Additionally, 765 putative transcription factor binding sites (TFBS) were identified that overlap with PTSD-associated CpG sites. Elucidation of the evolutionary history of PTSD-associated CpG sites may provide insights into the function and origin of epigenetic potential in trauma responses, generally, and PTSD, specifically. The human capacity to respond to trauma with stable physiologic and behavioral changes may be due to epigenetic potentials that are shared among many mammalian species.